2011
DOI: 10.1177/0091270010388033
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A5*3 Affects Plasma Disposition of Noroxycodone and Dose Escalation in Cancer Patients Receiving Oxycodone

Abstract: The aim of this study was to evaluate the plasma dispositions of oxycodone and its demethylates and dose escalation based on genetic polymorphisms of CYP2D6, CYP3A5, ABCB1, and OPRM1 in cancer patients receiving oxycodone. Sixty-two Japanese cancer patients receiving oxycodone extended-release tablets were enrolled. Predose plasma concentrations (C(12)) of oxycodone, noroxycodone, and oxymorphone were determined at the titrated dose. Daily oxycodone escalation rate was evaluated as the opioid escalation index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
4
25
1
Order By: Relevance
“…Among these is oxycodone (Naito et al, 2011), and the data reported in this study are consistent with the oxycodone clinical data. However, previously reported data showed that recombinant CYP3A5 had a higher intrinsic clearance for oxycodone N-demethylation than CYP3A4 (Lalovic et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Among these is oxycodone (Naito et al, 2011), and the data reported in this study are consistent with the oxycodone clinical data. However, previously reported data showed that recombinant CYP3A5 had a higher intrinsic clearance for oxycodone N-demethylation than CYP3A4 (Lalovic et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with the in vitro findings that CYP2C19 and UGT1A1 play a minor role in the overall clearance from the body. While CYP3A enzymes, especially CYP3A4, are clearly important in the metabolism of axitinib, the lack of correlation of pharmacokinetic variability with specific genotypes of CYP3A is consistent with the lack of phenotype-genotype correlations reported for other CYP3A substrates such as diltiazem, midazolam, nifedipine, and oxycodone (Floyd et al, 2003;Kharasch et al, 2007;Tomalik-Scharte et al, 2008;Naito et al, 2011;Haas et al, 2013;Zheng et al, 2013), where the pharmacokinetic variability can be attributed to the inherent range of CYP3A4 expression in the population, regardless of polymorphism. Additionally, investigations of pharmacokinetic variability seen in the clinic for axitinib, in lieu of the putative in vitro data supporting the prominent CYP3A4 role in axitinib clearance, include CYP3A4*22 polymorphism assessment from the collected genotyping samples.…”
Section: Discussionsupporting
confidence: 54%
“…Conversely, another clinical study of 76 motherinfant breast feeding pairs found mothers carrying at least one copy of the ABCB1 2677T variant had an increased risk of experiencing oxycodone-induced sedation themselves (114). Yet another clinical study found that cancer patients with the C3435T polymorphism of ABCB1 had little effect on the plasma disposition of oxycodone (115). The clinical implications of these variant alleles on P-gp function need further investigations to decipher their impact on opioids that are Pgp substrates.…”
Section: Oxycodonementioning
confidence: 99%
“…As with morphine, there does not appear to be a clear consensus on the role of ABCB1 polymorphisms in the PK and PD of oxycodone (113)(114)(115), fentanyl (132)(133)(134), or methadone (155-162, 164, 165). The reasons behind this apparent lack of clarity may be complex, and possibly involve the geographic distribution of patients enrolled as well as the polymorphisms selected for investigation.…”
Section: Transporter Polymorphismsmentioning
confidence: 99%